Design and development of a temperature measurement system based on battery powered single board computer - Koh, Hui Ping (Nanyang Technological University, 2021)
“A temperature measurement system based on battery powered single board computer” project focus on building a temperature measurement system that would allow the user to measure and store temperature data effortlessly especially in times epidemics. The project comprises of 3 components: Raspberry Pi, temperature sensor and Liquid Crystal Display (LCD). Raspberry Pi 3B+; a single board Linux computer will be used to run the necessary coding that is required for this project. Python programming language is used for the coding to achieve 3 objectives, mainly measuring, displaying, and storing the temperature data. In this project, DB18S20 Temperature sensor will be used along with 1.44-inch LCD HAT and Raspberry Pi. Temperature value will be shown in the LCD after the sensor detects the user’s body temperature, it would update the value to as soon as there is a detection of changes in the temperature from the sensor. The user would only have to holds the temperature sensor for roughly about 10 seconds, then the temperature data would automatically be stored according to its date into Raspberry Pi.